2014
DOI: 10.1007/s00268-014-2652-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Laparoscopic Splenectomy in the Setting of Hypersplenism Secondary to Liver Cirrhosis: Ten Years’ Experience

Abstract: It is safe and feasible to perform LS on patients with hypersplenism secondary to liver cirrhosis. In the procedure of SLELS, we highlight the importance of sufficient elevation the upper pole of the spleen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although laparoscopic splenectomy seems safe and feasible also in patients with platelets <10 × 10 9 /l with meticulous surgical technique (Cai et al , ), other studies have suggested an increased risk of bleeding with platelets <20 × 10 9 /l (Keidar et al , ). In patients responsive to a short‐course of IVIg or other medical therapy, we suggest to increase platelet count before surgery to above 30–50 × 10 9 /l.…”
Section: Consolidated Results Of Splenectomymentioning
confidence: 99%
“…Although laparoscopic splenectomy seems safe and feasible also in patients with platelets <10 × 10 9 /l with meticulous surgical technique (Cai et al , ), other studies have suggested an increased risk of bleeding with platelets <20 × 10 9 /l (Keidar et al , ). In patients responsive to a short‐course of IVIg or other medical therapy, we suggest to increase platelet count before surgery to above 30–50 × 10 9 /l.…”
Section: Consolidated Results Of Splenectomymentioning
confidence: 99%